Mindscapes: philosophy, science, and the mind - Carrier, Martin; Machamer, Peter K. (UVK, Universitätsverlag Konstanz, 1997)
Folk psychology and its liabilities / William Lycan -- The empirical naivete of the current philosophical conception of folk psychology / Barbara Von Eckardt -- Philosophy and folk psychology / John Haugeland -- Meanings as conceptual structures / Peter Gärdenfors -- Comment on Gärdenfors' "Meanings as conceptual structures" / Hans Rott -- Reinverting the spectrum / C.L. Hardin -- Explanations of colors : a comment to Hardin / Peter Machamer -- Is the naturalization of qualitative experience possible or sensible? / Maritine Nida-Rümelin -- Comment on Nida-Rümelin's paper "Is the naturalization of qualitative experience possible or sensible?" / Holm Tetens -- Explaining voluntary action : the role of mental content / Wolfgang Prinz -- The conscious and the non-conscious : philosophical implications of neuropsychology / Ran Lahav -- On the difficulty of keeping consciousness intact : Lahav on conscious integration and causality / Martin Carrier -- On cognitive luck : externalism in an evolutionary frame / Ruth Garrett Millikan -- Fitting the frame to the picture : comments on Millikan's "Cognitive luck : externalism in an evolutionary frame" / Bradley E. Wilson -- Animal cognition and animal minds / Colin Allen -- Connectionism, dynamics, and the philosophy of mind / Tim van Gelder -- Supervenience, emergence, and realization in the philosophy of mind / Jaegwon Kim -- Comment on J. Kim's "Supervenience, emergence and realization in the philosophy of mind" / Paul Hoyningen-Huene -- Property physicalism, reduction and realization / Ansgar Beckermann -- Over hundred years of psychoanalytic theory and therapy : retrospect and prospect / Adolf Grünbaum.
"The present volume has grown out of the Third Pittsburgh-Konstanz Colloquium held in Konstanz, May 17-20, 1995"--Pref. - Includes bibliographical references and index. - Description based on print version record
Keywords: Electronic book; Electronic books; Konferenzschrift; Philosophy of Mind